Kekuatan Eksekusi Putusan Peradilan Agama terhadap Kewajiban Ayah Menafkahi Anak Pasca Perceraian. - Arbani, Tri Suhendra (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2020)
"This study aims to examine two important issues, namely to examine all the related rules and legal basis for the obligation of a father to provide for a child after divorce and the power of the execution of the religious court to respect the livelihoods of a child after divorce. The research method used is normative legal research. The approach used is the statute approach. From the results of the study it can be concluded that the regulations regarding the obligation to support children by the father after divorce do not provide strict sanctions so that there are many cases where the father does not fulfill this obligation. the need for a system or mechanism after the ruling of a religious court where the obligations of a father can be fulfilled such as automatically deducting wages every month, taking part of his father's assets which are then paid at once at the beginning, taking collateral for assets so that he can fulfill his father's obligations every month, and giving sanctions that are assertive".